The understanding of emotion among young Chinese children. (September 2018) - Tang, Yulong; Harris, Paul L.; Pons, Francisco; Zou, Hong; Zhang, Wenjuan; Xu, Qunxia
The development of emotion understanding in young Chinese preschoolers was examined. The overall developmental trend, as measured by the Test of Emotion Comprehension (TEC), proved similar to that found among preschoolers in Western Europe. However, Chinese children performed better at understanding the distinction between real and apparent emotion and worse at understanding the connection between reminders and emotion. Children's theory of mind and verbal ability were significant predictors of their ability to understand emotion.